Conservation of Mouse Models Through Embryo Freezing. Issue 4 (11th December 2014) - Guan, Mo; Bogani, Debora; Marschall, Susan; Raspa, Marcello; Takeo, Toru; Nakagata, Naomi; Fray, Martin
Abstract : The ability to interrogate the entire coding sequence of the mouse combined with the tools to manipulate the genome has firmly established the mouse as the model organism of choice for studying the causes of human disease. Consequently, a huge number of novel mouse models are generated each year to support active research programs. However, it is neither ethically justifiable, nor economically viable to maintain mouse colonies on the shelf that are not part of active research programs. This means that novel mouse lines have to be preserved in some way. If this is not done and the line is simply killed off, the genetics will be lost to future generations of scientists. This article describes the current practices used in cryopreservation laboratories to archive and recover mouse embryos frozen using controlled‐rate freezing and vitrification techniques. © 2014 by John Wiley & Sons, Inc.